Parametric Study on Passive Suspension of Light Rail Vehicle (LRV) - Mohd Izwan Hadi b. Ismail @ Mansor, Mohd Izwan (Universiti Teknologi PETRONAS, 2008)
This research project proposes the passive suspension of light rail vehicle (LRV) to be studied parametrically. The system is modelled as a multi-body dynamic model and used passive systems suspension which is the simplest and common type of suspensions to isolate disturbance from the track to the car-body. One model of light rail vehicle (LRV) will be selected and form a mathematical model for analysis purpose. The equation of motion will be develop from the mathematical model and then from the equation of motion the matrices of the LRV systems are derived, and it will be translated it into MATLAB language. The response of the system under varying parameters of suspension will be simulated computationally by using MATLAB. In this research, the parameters are divided in 5 cases, which is for case 0 is using the nominal parameters, case 1 the nominal parameters is reduced by 20%, case 2 the nominal parameter is reduced by 50%, case 3 the nominal parameters is increased by 20% and for case 4 the nominal parameters is increased by 50%. For the results, the maximum suspension deflections and the stability of each car-body on random gradient track will be discussed.